Urine Desmosine as a Novel Biomarker for Bronchopulmonary Dysplasia and Postprematurity Respiratory Disease in Extremely Preterm or Low Birth Weight Infants - Hirata, Katsuya; Nishikawa, Masanori; Nozaki, Masatoshi; Kitajima, Hiroyuki; Yanagihara, Itaru; Wada, Kazuko; Fujimura, Masanori (American Journal of Perinatology, 2022)
Objective This study aimed to evaluate whether elevated urine desmosine levels at 3 weeks of age were associated with severe radiological findings, bronchopulmonary dysplasia (BPD), and post-prematurity respiratory disease (PRD) in extremely preterm (EP) or extremely low birth weight (ELBW) infants.Study Design This study recruited 37 EP (22–27 completed weeks) or ELBW (<1,000 g) infants. Urine was collected between 21 and 28 postnatal days, and desmosine was measured using an enzyme-linked immunosorbent assay kit; the urine creatinine level was also measured. Bubbly/cystic lungs were characterized by emphysematous chest X-rays on postnatal day 28. Furthermore, provision of supplemental oxygen or positive-pressure respiratory support at 40 weeks' postmenstrual age defined BPD, and increased medical utilization at 18 months of corrected age defined PRD. The desmosine/creatinine threshold was determined by receiver operating characteristic analysis. The adjusted risk and 95% confidence interval (CI) for elevated urine desmosine/creatinine levels were estimated by logistic regression analysis.Results Elevated urine desmosine/creatinine levels higher than the threshold were significantly associated with bubbly/cystic lungs (8/13 [61.5%] vs. 2/24 [8.3%], p = 0.001), BPD (10/13 [76.9%] vs. 8/24 [33.3%], p = 0.02), and PRD (6/13 [46.2%] vs. 2/24 [8.3%], p = 0.01). After adjusting for gestational age, birth weight, and sex, the urine desmosine/creatinine levels were significantly higher in those who were highly at risk of bubbly/cystic lungs (odds ratio [OR], 13.2; 95% CI, 1.67–105) and PRD (OR, 13.8; 95% CI, 1.31–144).Conclusion Elevated urine desmosine/creatinine levels on the third postnatal week were associated with bubbly/cystic lungs on day 28 and PRD at 18 months of corrected age in EP or ELBW infants.Key Points
Keywords: biomarker; bronchopulmonary dysplasia; desmosine; extremely low birth; extremely preterm infant